Opening of the Skouw and Wutung Vanimo Cross-Border Border Crossing Land Road Crossing and Its Sustainability for the Pacific Region - Melyana Ratana Pugu (Eduvest - Journal of Universal Studies, 2024)
This study aims to provide an in-depth analysis and clear data regarding the opening of land roads for land crossings, vehicles, goods and services, and people at the Northern Papua-Papua New Guinea border, specifically at the Skouw National Border Post connected to Vanimo, Papua New Guinea. The opening of this crossing lane has both positive and negative impacts on the crossing area. Therefore, it is crucial to conduct this study from a perspective beyond the Westphalian System, which focuses not only on maintaining national sovereignty but also on the unification of borders or a de-borderless approach. This perspective aims to advance the communities around the border of the two countries and provide significant benefits. The method used in this study is a qualitative research method, which explains the border phenomenon between the two countries with valid data obtained through primary and secondary sources, ensuring clear and accurate data. The results indicate that the opening of crossings for goods, services, and people at the Skouw-Vanimo border will enhance economic activities in both countries, increase socio-cultural interactions among border communities, strengthen bilateral relations, and establish the region as a hub for economic and trade activities with other Pacific countries. Moreover, it will reduce tensions among Pacific countries, promote strategic partnerships due to enhanced connectivity in the Pacific region, and even extend to the Indo-Pacific. This study highlights the potential benefits of a de-borderless approach to border management, emphasizing the need for cooperative development to maximize the positive impacts on the communities involved.